2022
DOI: 10.3390/ijerph192315879
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Public Health Education on Migrant Workers’ Medical Service Utilization

Abstract: Based on the dynamic monitoring survey data of China’s migrant population (CMDS) in 2017, this study analyzes the impact of public health education on migrant workers’ medical service utilization. The study found that public health education can significantly promote the utilization of migrant workers’ medical services and has a greater effect on the older generation groups, those who received secondary and higher education, and those working in first-tier cities. By distinguishing different types of public he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 29 publications
1
5
0
Order By: Relevance
“…Tis is consistent with other studies that show a greater impact of external interventions on elderly [55]. However, studies found that younger migrants received more health education [47], and they had lower health care utilization [56]. Tese studies help understand the diferential efects of health education among migrants of diferent ages.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Tis is consistent with other studies that show a greater impact of external interventions on elderly [55]. However, studies found that younger migrants received more health education [47], and they had lower health care utilization [56]. Tese studies help understand the diferential efects of health education among migrants of diferent ages.…”
Section: Discussionsupporting
confidence: 89%
“…Tirdly, health education is more efective for migrants with higher levels of education. Socioeconomic status has been shown to be associated with health status [57], and migrants with higher levels of education have a better health education [47], as well as higher levels of utilization of medical services [56]. Te other possible explanation is that migrants with higher levels of education have a higher level of health literacy, value health more, have a better understanding of health knowledge, and also have a stronger ability to improve their health [21], and therefore, health education is more efective for them compared to those without higher education.…”
Section: Discussionmentioning
confidence: 99%
“…For the second major independent variable, we selected seven out of the nine types of health education programs based on the existing research literature and knowledge of the most prevalent health issues among the vulnerable migrant population in China. These seven types of health education included occupational disease, venereal disease/AIDS, reproductive health, mental health, chronic health, maternal and child health, and self-rescue in public emergencies [ 43 , 44 , 45 , 46 , 47 , 48 , 49 ]. Each type was transformed into a dummy variable to investigate the relationship between the type of disease prevention education and the health status of migrants.…”
Section: Methodsmentioning
confidence: 99%
“…The NEPHS has witnessed an expansion of its service categories from 9 in 2009 to 14 in 2017, and the per capita financial subsidy standard has risen from ¥15 in 2009 to ¥89 in 2023. [4][5][6] Several studies have investigated the beneficial impacts of NEPHS utilisation on various aspects of the floating population, such as the treatment and control of chronic diseases, 7 8 health status, [9][10][11][12] accessibility and utilisation of healthcare services, [13][14][15] multidimensional poverty 16 and settlement intentions. 17 While the NEPHS attempts to ensure that all floating population and registered residents have equal access to NEPHS awareness and utilisation, most floating population is excluded from NEPHS in the initial stage of policy implementation, and they are unable to access basic public health services as registered residents.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%